Cultural аnd Natural Heritage оf Djerdap - Lost History оr Potential for Sustainable Development? - Nikolić, Marko; Šćekić, Jelena (Arhitektura i urbanizam, 2022)
The Roman Limes, the former natural border of the Roman Empire, has been recognized as a cultural landscape with exceptional universal values of international importance by the relevant organization for the protection of cultural and natural heritage - UNESCO. The Danube River is an integral part of the Roman Limes, a testimony to the culture and traditions of the peoples who lived on the banks of the Danube, as well as cultural heritage in general. Within the part of the Danube River that passes through the Republic of Serbia, the Djerdap segment stands out. It includes sites of different historical periods (prehistoric, ancient and medieval) and is significant cultural heritage on an international level. However, most of the sites are underwater as a result of the construction of the Djerdap Hydroelectric Power Plant. Consequently, insufficient access to its cultural heritage has led to its insufficient presentation and promotion, but also a lack of information about the existence of the cultural heritage. Therefore, the main goals of this paper are to spread knowledge about Djerdap’s cultural and natural heritage, to promote its importance, to identify potential for integrating the cultural heritage into contemporary trends through the affirmation of cultural routes, and to establish sustainable development of the cultural landscape. The results of the research are presented through an urban architectural project that represents the sublimation of critical attitudes formed with regard to the protection, presentation and promotion of cultural heritage. The project draws from a literature analysis, case studies and examples of good practice relevant to the research. The expected results of the research include raising awareness of the importance of Djerdap’s cultural heritage through promoting a cultural route and forming a potential model for the use of its cultural heritage in the process of establishing sustainable development of the cultural landscape.